Do social protection programmes affect the burden of breast and cervical cancer? A systematic review - Ligia Gabrielli; Sheila M. Alvim Matos; Ana Luísa Patrão; Emanuelle F. Góes; Maria da Conceição C. Almeida; Greice M.S. Menezes; Isabel dos-; Gulnar Azevedo e Silva; Maria Teresa Bustamante-Teixeira; Mauricio L. Barreto; Srinivasa Vittal Katikireddi; Alastair H. Leyland; et al. (Elsevier, 2024)
Background: Socioeconomic conditions are strongly associated with breast and cervical cancer incidence and mortality patterns; therefore, social protection programmes (SPPs) might impact these cancers. This study aimed to evaluate the effect of SPPs on breast and cervical cancer outcomes and their risk/protective factors. Methods: Five databases were searched for articles that assessed participation in PPS and the incidence, survival, mortality (primary outcomes), screening, staging at diagnosis and risk/protective factors (secondary outcomes) for these cancers. Only peer-reviewed quantitative studies of women receiving SPPs compared to eligible women not receiving benefits were included. Independent reviewers selected articles, assessed eligibility, extracted data, and assessed the risk of bias. A harvest plot represents the included studies and shows the direction of effect, sample size and risk of bias. Findings: Of 17,080 documents retrieved, 43 studies were included in the review. No studies evaluated the primary outcomes. They all examined the relationship between SPPs and screening, as well as risk and protective factors. The harvest plot showed that in lower risk of bias studies, participants of SPPs had lower weight and fertility, were older at sexual debut, and breastfed their infants for longer. Interpretation: No studies have yet assessed the effect of SPPs on breast and cervical cancer incidence, survival, or mortality; nevertheless, the existing evidence suggests positive impacts on risk and protective factors.